Karakteristik Gambaran Histologis Paru-Paru Pasien COVID-19 - Gaghaube, Andre M.; Kaseke, Martha M.; Kalangi, Sonny J. R. (Universitas Sam Ratulangi, 2021)
Abstract: Severe acute respiratory syndrome coronavirus (SARS-COV-2) is an infectious disease caused by coronavirus. Coronavirus (COVID-19) first attacks the upper respiratory system such as the nose, mouth, throat even the lungs and can trigger symptoms of fever and cough (pneumonia) resulting in changes in lung organ tissue during histological examination. This study aimed to determine the characteristics of the histological picture of the lungs of COVID-19 patients. This research uses a literature review research method. Based on 12 research reports analyzed in this research, the most common characteristic of histological features found in 12 research report journals is the finding of a diffuse alveolar damage pattern. Diffuse alveolar damage is a condition of acute lung injury which is accompanied by an acute phase with edema, a hyaline membrane, and inflammation followed by an organizing phase, where there is hyperplasia of type II pneumocytes, there is also fibrin or intra-alveolar protein. In conclusion, the characteristics of the histological features of the lungs most commonly found in COVID-19 patients are the findings of a diffuse alveolar damage pattern, which is a condition of acute lung injury and an acute phase with edema, hyaline membrane, and inflammation followed by an organizing phase, namely there is hyperplasia of type II pneumocytes, there is also fibrin or intra-alveolar proteinKeywords: lung histology, COVID-19. Abstrak: Severe acute respiratory syndrome coronavirus (SARS-COV-2) adalah sebuah penyakit menular yang disebabkan oleh coronavirus. Coronavirus (COVID-19) pertama kali menyerang sistem pernapasan bagian atas seperti hidung, mulut, tenggorokan bahkan sampai ke paru – paru dan dapat memicu gejala demam dan batuk (pneumonia) sehingga terjadi perubahan jaringan organ paru – paru pada saat dilakukan pemeriksaan histologi. Penelitian bertujuan untuk mengetahui karakteristik gambaran histologis paru – paru pasien COVID-19. Penelitian ini menggunakan metode penelitian literature review. Berdasarkan 12 laporan penelitian yang di analisis pada penelitian ini, karakteristik gambaran histologis yang paling umum ditemukan pada 12 jurnal laporan penelitian yaitu terdapat temuan pola diffuse alveolar damage. Diffuse alveolar damage merupakan kondisi cedera paru akut atau acute lung injury yang disertai dengan fase akut dengan adanya edema, terdapat membran hialin, dan inflamasi di ikuti dengan fase pengorganisasian yaitu terdapat hiperplasia pneumosit tipe II, juga terdapat fibrin atau protein intra-alveolar. Sebagai simpulan, karakteristik gambaran histologis paru – paru yang paling umum ditemukan pada pasien COVID-19 adalah temuan pola diffuse alveolar damage yang merupakan kondisi cedera paru akut atau acute lung injury serta fase akut dengan adanya edema, terdapat membran hialin, dan inflamasi di ikuti dengan fase pengorganisasian yaitu terdapat hiperplasia pneumosit tipe II, juga terdapat fibrin atau protein intra-alveolarKata Kunci: histologi paru, COVID-19